G372(P) Early relapse of atypical HUS following ABO incompatible living related paediatric renal re-transplant successfully treated with eculizumab. (7th April 2014) - Stojanovic, J; Mamode, N; Knapp, K; Wright, E; Hothi, D; Rees, L; Waters, A; Sebire, NJ; Marks, SD
Abstract : Aim: We present a paediatric case of successful treatment of an early relapse of atypical haemolytic uraemic (aHUS) syndrome following ABO incompatible (ABOi) living related renal transplant using eculizumab. The female patient presented at 3.8 years of age with clinical aHUS confirmed genetically as complement factor I mutation (heterozygous for CFI c.1216C >T, p.(Arg406Cys) in patient (who had Factor H antibodies) and asymptomatic mother. She was initially treated with forty plasma exchange sessions. Four months after presentation, she commenced peritoneal dialysis converted to home haemodialysis. At 8.8 years of age, a deceased donation after cardiac death en bloc renal transplant failed to perfuse and was removed at the time of transplantation. Methods: Prospective case study of paper and electronic records. Results: She received an ABOi live related kidney transplant from father at 9.3 years using quadruple immunosuppression (basiliximab, mycophenolate mofetil, tacrolimus, corticosteroids) with B lymphocyte depletion (intravenous rituximab 375 mg/m one month pre-transplantation) with 0% calculated reaction frequency. Recipient and donor (father) blood groups were O and A respectively with anti-A titres of 1 in 128 pre-transplantation. Four sessions of immunoadsorption reduced anti-A titres to 1 in 4 at time of transplant. Six hours post-transplant, she received the first dose of intravenous eculizumab 600 mg as she showed signs of recurrence of aHUS with allograft dysfunction, LDH 1291 U/l, haemoglobin of 83 g/l and thrombocytopenia at 109 × 10 9 /l. LDH rose to maximum value of 3334 U/l on day 2 post transplant with ongoing anaemia and thrombocytopenia (49 g/l and 82 ×  10 9 /l respectively) with a second dose of eculizumab administered with good clinical response: reduction in LDH and normalisation of Hb and platelets. Renal allograft function improved at 8 days post-transplant and she continues on regular eculizumab infusions with histopathological evidence of thrombotic microangiopathy. Six weeks post transplant, renal function has stabilised with plasma creatinine of 75–93 μmol/l (eGFR of 45–55 mls/min/1.73 m 2 ), EBV reactivation, BK viraemia, normalisation of LDH 486 U/l, Hb 120 g/l and platelets 353 ×  10 9 /l; negative anti-A titres and HLA antibodies Conclusions: This is the first report of a paediatric ABOi living related renal transplantation in whom early relapse of a HUS was successfully treated with eculizumab.